1987
DOI: 10.1042/bj2420367
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates of tocopherol biosynthesis in the unicellular alga Scenedesmus obliquus. The presence of three isomeric methylphytylbenzoquinones

Abstract: Three isomers of methylphytylbenzoquinone have been isolated from lipids of the unicellular alga Scenedesmus obliquus, the most abundant being 2-methyl-6-phytylbenzoquinone (65% of the total). The 2-methyl-3-phytyl and 2-methyl-5-phytyl isomers amounted to 8 and 27% respectively. Previously problems have been encountered in the separation of the 3-phytyl and the 6-phytyl isomers, but in the present study it was found that they separated readily as quinols. Phytyl plastoquinone was also found and the relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The results of these experiments clearly showed that the SLL0418 protein was capable of methylating reduced or oxidated MPBQ with similar efficiency (specific activity=395±40 pmol/mg protein/h and 404±20 pmol/mg protein/h for reduced and oxidized MPBQ, respectively). The radiolabeled reduced and oxidized products migrated to the reported R f for 2,3‐dimethyl‐6‐phytylbenzoquinol and quinone [8], respectively (data not shown).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The results of these experiments clearly showed that the SLL0418 protein was capable of methylating reduced or oxidated MPBQ with similar efficiency (specific activity=395±40 pmol/mg protein/h and 404±20 pmol/mg protein/h for reduced and oxidized MPBQ, respectively). The radiolabeled reduced and oxidized products migrated to the reported R f for 2,3‐dimethyl‐6‐phytylbenzoquinol and quinone [8], respectively (data not shown).…”
Section: Resultsmentioning
confidence: 85%
“…A mixture of six different isomers of methylphytylbenzoquinone was synthesized as described by Henry et al [8]. 250 μg of the mixed isomer preparation was suspended in ethylether and oxidized by adding 100 mg of silver oxide and incubating for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate MPBQ and a standard for the reaction product 2,3-dimethyl-5-phytylbenzoquinol for the methyltransferase assay were prepared as described previously Henry et al, 1987). Cell pellets expressing Anab-VTE3, At-VTE3, or vte3-1 protein were thawed on ice and resuspended in 4 mL of extraction buffer XB [10 mM Hepes-KOH, pH 7.8, 5 mM DTT, 1 mM 4-(2-aminoethyl) benzenesulfonyl fluoride, 0.1 mM aprotinin, and 1 mg/mL leupeptin].…”
Section: -Methyl-6-phytylbenzoquinol (Mpbq) Methyltransferase Enzymementioning
confidence: 99%
“…Chemical synthesis and purification of 2-methyl-6-phytylbenzoquinone substrate were as reported by Peddibhotla et al (2002). 2-Methyl-6-solanylbenzoquinone substrate was extracted and purified from iris bulbs as described by Henry et al (1987).…”
Section: Escherichia Colimentioning
confidence: 99%